Numerical simulation on the elucidation of wake flow structure behind a single Quarter Elliptic-Wedge Spire - Muhammad Arifuddin, Fitriady; Nurizzatul Atikha, Rahmat; Ahmad Faiz, Mohammad (EIT Digital Library, 2022)
The urban heat island phenomenon has become a significant concern worldwide and its impact can be devastated. One of the most common factors of the UHI is poor ventilation i.e. the incapability of airflow to reduce the temperature in an urban area due to velocity deficit from a poorly designed city layout. Hence, a good understanding of the interaction between the wake flow behind a building and the urban boundary layer is necessary. Therefore, a study investigates the wake flow structure behind a single spire, which imitates a skyscraper, and its aerodynamic interaction with the smooth wall boundary layer based on CFD by utilising OpenFOAM® with the k-ε turbulence model has been conducted. The lateral velocity profile was extracted and analysed to observe the velocity deficit profile. It was found that the lateral velocity profile of the current study is aligned with the previous WT experimental data. The turbulence generated by the spire has the capability to preserve the wake flow against the recovery process both in vertical and streamwise directions. Furthermore, the distance required by the wake flow to be fully recovered is estimated to be around 40S in the streamwise direction. Finally, based on the wake flow and gradient diffusion model relation, it can be concluded that the flow structure above the BLH is specified as a typical 2D wake of a bluff body in a free stream for the near wake region only.